5u-10=-3u-10

Simple and best practice solution for 5u-10=-3u-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5u-10=-3u-10 equation:


Simplifying
5u + -10 = -3u + -10

Reorder the terms:
-10 + 5u = -3u + -10

Reorder the terms:
-10 + 5u = -10 + -3u

Add '10' to each side of the equation.
-10 + 10 + 5u = -10 + 10 + -3u

Combine like terms: -10 + 10 = 0
0 + 5u = -10 + 10 + -3u
5u = -10 + 10 + -3u

Combine like terms: -10 + 10 = 0
5u = 0 + -3u
5u = -3u

Solving
5u = -3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '3u' to each side of the equation.
5u + 3u = -3u + 3u

Combine like terms: 5u + 3u = 8u
8u = -3u + 3u

Combine like terms: -3u + 3u = 0
8u = 0

Divide each side by '8'.
u = 0

Simplifying
u = 0

See similar equations:

| p=h+5h/-3+y | | (y-3)(-5y^2+6y+2)= | | 7x-15(x-7)=9x | | 300x=1200 | | (3y-5)+(6y+20)=135+y | | 2+a/4-1 | | -5x+6=-x-2 | | 5x^2+5x+1=0 | | 34+2y-11=10y-13-2y | | (x+15)+(x-23)=44 | | p-18=15 | | 23x+x^2=12 | | 2x+3=-2 | | .2=.07+x(.12) | | x+3-14x+11=3x-12-10x | | x/22+3.2=16 | | 30x+18/x=-48 | | n+23= | | x/27=35 | | 36-9x=45 | | x-36=30 | | 6a+3a-5a-b= | | x+29=12 | | x-3x-6=-x | | 12a^3+39a^2-36a= | | x+8x-2=3x | | y=1.2x-3.8 | | 100-15=2.5h | | Z/3=5/3 | | 22=3x+4 | | 50x=3 | | -48=6(a) |

Equations solver categories